2014
DOI: 10.1075/pbns.247.12han
|View full text |Cite
|
Sign up to set email alerts
|

Besides as a connective

Abstract: This paper shows, on the basis of a comparison of learner corpus data with written and spoken native corpus data, that learners tend to use spoken features when organising their academic writing. Possible explanations are offered to account for this problem of register confusion, including L1 transfer, L2 instruction and developmental factors. Suggestions are also made to help learners become more aware of register variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Unlike previous studies which focus their attention on a particular marker and investigate the coherence relations associated with it (Fillmore et al, 1988;Hannay et al, 2014;Noordman, 2001), Iza Erviti (2015Erviti ( , 2021 has identified and studied the family of complementary alternation discourse constructions, providing a fine-grained description of its members. This constructional family spans a range of configurations containing connectors such as let alone, much less, even less, never mind, not to mention, and to say nothing of, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous studies which focus their attention on a particular marker and investigate the coherence relations associated with it (Fillmore et al, 1988;Hannay et al, 2014;Noordman, 2001), Iza Erviti (2015Erviti ( , 2021 has identified and studied the family of complementary alternation discourse constructions, providing a fine-grained description of its members. This constructional family spans a range of configurations containing connectors such as let alone, much less, even less, never mind, not to mention, and to say nothing of, among others.…”
Section: Introductionmentioning
confidence: 99%
“…However, these authors study the construction in isolation and do not take into account other constructions with a related meaning. Similarly, from a functionalist perspective, Hannay, Martínez Caro, and Mackenzie (2014) offer an analysis of the connective besides, but still fail to explore its interconnections with other semantically-related markers. This weakness in the study of explicit discourse constructions has been pointed out by other authors such as Mairal and Ruiz de Mendoza (2009), and Ruiz de Mendoza and Gómez González (2014).…”
Section: Introductionmentioning
confidence: 99%